The transcriptional and cellular landscape of cognitive resilience to Alzheimer’s disease - Khera, Nina; Raju, Ravikiran M.; Lipton, Stuart A. (Frontiers in Molecular Neuroscience, 2025)
It is estimated that 5%–40% of patients with pathological features of Alzheimer’s disease (AD) maintain normal cognitive health throughout their lifetimes, a phenomenon known as cognitive resilience. Studies have identified many factors that contribute to a patient’s capacity for resilience, with those that modulate gene expression being the most dynamic, adaptable, and potentially addressable as targets for future drug development. In patients cognitively resilient to AD and AD-related dementias (ADRD), transcriptional changes within specific cell types serve to preserve the processes most critical to cognitive function within each cell, exerting protective effects on other cell types as well via non-cell autonomous effects. Key themes in preserved cognitive function include maintenance of synaptic stability and function, dampening neuronal hyperexcitability, reducing misfolded protein accumulation, increasing myelination, and countering neuroinflammation. With future research on the most upstream and impactful transcriptional drivers, there lies immense potential for both therapeutics to address AD and a greater fundamental understanding of AD and the brain.